Pengabdian Masyarakat: Screening Status Gizi dan Edukasi pada Remaja di Bimbingan Belajar X Kota Tasikmalaya - Panji Raraswati, Rhela; Ratna Hidayani, Wuri; Ifah Latifah, Ade (JURNAL ABDIMAS KESEHATAN TERPADU, 2025)
Adolescents are a vulnerable group to nutritional problems due to increased nutritional needs during growth. The 2018 Basic Health Research (Riskesdas) reported a prevalence of undernutrition at 12.8% and overweight at 16% among Indonesian adolescents. Similar conditions were also found in West Java and Tasikmalaya City, indicating the need for early detection and nutrition education. This community service activity aimed to assess the nutritional status of adolescents at Learning Center X in Tasikmalaya City and to improve their knowledge of healthy eating patterns. The methods included anthropometric measurements (weight, height, body mass index, and mid-upper arm circumference) and nutrition education through interactive counseling using QR-based media. The target participants were 10 adolescents aged 13–18 years enrolled at the learning center. The results showed that 30% of adolescents were undernourished based on BMI-for-age, while 50% experienced Chronic Energy Deficiency (CED) based on MUAC. Nutrition education was conducted after the screening, and participants demonstrated enthusiasm and improved understanding of the importance of breakfast, balanced diet, and stunting prevention. This activity highlights that simple screening can identify adolescents at risk of undernutrition and serves as an effective medium for nutrition education. In conclusion, nutritional problems among adolescents remain high and may impact long-term health. It is recommended to conduct regular monitoring through adolescent health posts or school health units and strengthen collaboration with schools and primary health centers to ensure program sustainability.